Permeabilization of Haematococcus pluvialis and solid-liquid extraction of astaxanthin by CO2-based alkyl carbamate ionic liquids - Khoo, K.S. (Elsevier B.V., 2021)
Haematococcus pluvialis (H. pluvialis) microalgae are well known for their high content of astaxanthin, which is a super potent antioxidant with various remedial effects. Ionic liquids (ILs) have been proposed as a promising solvent to permeabilize the robust microalgal cell wall for an effective extraction of bioactive compounds. Nonetheless, the removal of ILs from the extracted compounds requires the additional treatment steps that complicate the overall extraction process and the recycling of ILs. To address these shortcomings, we demonstrated a sustainable extraction system that utilizes CO2-based alkyl carbamate ILs to permeate H. pluvialis cells and extract astaxanthin. This class of ILs is readily distillable for an easy recovery of ILs from the extraction medium. Among the tested CO2-based alkyl carbamate ILs dimethylammonium dimethylcarbamate (DIMCARB), dipropylammonium dipropylcarbamate (DPCARB), dibutylammonium dibutylcarbamate (DBCARB) and diallyammonium diallycarbamate (DACARB), DIMCARB gave the best performance of astaxanthin extraction. The optimized extraction conditions 100% (w/w) of DIMCARB, 75 min and 45 Â°C resulted in the high yield of astaxanthin (27.99 mg/g). The capability of DIMCARB to permeabilize the amorphous trilayered structure of cell wall was verified by the presence of pores on the cell surface of H. pluvialis as shown in the microscope images. The performance and recyclability of DIMCARB extraction system were also evaluated by conducting three successive rounds of astaxanthin extraction with the recycled DIMCARB solutions. In addition, the antioxidant capacity of the extracted astaxanthin was well retained, showing that this type of distillable IL was suitable for the extraction of phytonutrients from algal source. Â© 2021 Elsevier B.V.